The Impact of Thermocycling on the Physico-mechanical Properties of SLA and DLP 3D-Printed Dental Ceramics: A Comparative Study - Nadia H Hasan (Dentistry 3000)
Objective: Three-dimensional (3D) printing technology is highly promising for producing nanoceramic resin dental restorations. However, the effects of environmental stressors on the structural integrity and clinical performance of these restorations require further elucidation. To investigate the effects of Stereolithography (SLA) and digital light processing (DLP) 3D printing technologies on the physical-mechanical properties of a 3D-printed resin material used in dental applications.